Non-metal-templated approaches to bis(borane) derivatives of macrocyclic dibridgehead diphosphines via alkene metathesis - Fiedler, Tobias; Barbasiewicz, Michał; Stollenz, Michael; Gladysz, John A. (Beilstein Journal of Organic Chemistry, 2018)
Two routes to the title compounds are evaluated. First, a ca. 0.01 M CH2Cl2 solution of H3B·P((CH2)6CH=CH2)3 (1·BH3) is treated with 5 mol % of Grubbs' first generation catalyst (0 °C to reflux), followed by H2 (5 bar) and Wilkinson's catalyst (55 °C). Column chromatography affords H3B·P(n-C8H17)3 (1%), H3B·P((CH2)13CH2)(n-C8H17) (8%; see text for tie bars that indicate additional phosphorus–carbon linkages, which are coded in the abstract with italics), H3B·P((CH2)13CH2)((CH2)14)P((CH2)13CH2)·BH3 (6·2BH3, 10%), in,out-H3B·P((CH2)14)3P·BH3 (in,out-2·2BH3, 4%) and the stereoisomer (in,in/out,out)-2·2BH3 (2%). Four of these structures are verified by independent syntheses. Second, 1,14-tetradecanedioic acid is converted (reduction, bromination, Arbuzov reaction, LiAlH4) to H2P((CH2)14)PH2 (10; 76% overall yield). The reaction with H3B·SMe2 gives 10·2BH3, which is treated with n-BuLi (4.4 equiv) and Br(CH2)6CH=CH2 (4.0 equiv) to afford the tetraalkenyl precursor (H2C=CH(CH2)6)2(H3B)P((CH2)14)P(BH3)((CH2)6CH=CH2)2 (11·2BH3; 18%). Alternative approaches to 11·2BH3 (e.g., via 11) were unsuccessful. An analogous metathesis/hydrogenation/chromatography sequence with 11·2BH3 (0.0010 M in CH2Cl2) gives 6·2BH3 (5%), in,out-2·2BH3 (6%), and (in,in/out,out)-2·2BH3 (7%). Despite the doubled yield of 2·2BH3, the longer synthesis of 11·2BH3 vs 1·BH3 renders the two routes a toss-up; neither compares favorably with precious metal templated syntheses.
Keywords: alkene metathesis; crystal structures; homeomorphic isomerization; hydrogenation; in/out isomers; metathesis; phosphine boranes

(untitled) - Shima, T.; Hampel, F.; Gladysz, J. A. (Angew. Chem., Int. Ed., 2004)
Angew. Chem. 2004, 116, 5653–5656. doi:10.1002/ange.200460534

(untitled) - Lang, G. M.; Shima, T.; Wang, L.; Cluff, K. J.; Skopek, K.; Hampel, F.; Blümel, J.; Gladysz, J. A. (J. Am. Chem. Soc., 2016)

(untitled) - Lang, G. M.; Bhuvanesh, N.; Reibenspies, J. H.; Gladysz, J. A. (Organometallics, 2016)

(untitled) - Lang, G. M.; Skaper, D.; Hampel, F.; Gladysz, J. A. (Dalton Trans., 2016)

(untitled) - Nawara, A. J.; Shima, T.; Hampel, F.; Gladysz, J. A. (J. Am. Chem. Soc., 2006)

(untitled) - Nawara-Hultzsch, A. J.; Stollenz, M.; Barbasiewicz, M.; Szafert, S.; Lis, T.; Hampel, F.; Bhuvanesh, N.; Gladysz, J. A. (Chem. – Eur. J., 2014)

(untitled) - Kharel, S.; Joshi, H.; Bhuvanesh, N.; Gladysz, J. A. (Organometallics, 2018)

(untitled) - Wang, L.; Hampel, F.; Gladysz, J. A. (Angew. Chem., Int. Ed., 2006)
Angew. Chem. 2006, 118, 4479–4482. doi:10.1002/ange.200601191

(untitled) - Wang, L.; Shima, T.; Hampel, F.; Gladysz, J. A. (Chem. Commun., 2006)

(untitled) - Estrada, A. L.; Jia, T.; Bhuvanesh, N.; Blümel, J.; Gladysz, J. A. (Eur. J. Inorg. Chem., 2015)

(untitled) - Hess, G. D.; Hampel, F.; Gladysz, J. A. (Organometallics, 2007)

(untitled) - Fiedler, T.; Bhuvanesh, N.; Hampel, F.; Reibenspies, J. H.; Gladysz, J. A. (Dalton Trans., 2016)

(untitled) - Hess, G. D.; Fiedler, T.; Hampel, F.; Gladysz, J. A. (Inorg. Chem., 2017)

(untitled) - Setaka, W.; Yamaguchi, K. (J. Am. Chem. Soc., 2013)
and earlier work cited therein.

(untitled) - Setaka, W.; Inoue, K.; Higa, S.; Yoshigai, S.; Kono, H.; Yamaguchi, K. (J. Org. Chem., 2014)

(untitled) - Setaka, W.; Higa, S.; Yamaguchi, K. (Org. Biomol. Chem., 2014)

(untitled) - Shionari, H.; Inagaki, Y.; Yamaguchi, K.; Setaka, W. (Org. Biomol. Chem., 2015)

(untitled) - Nishiyama, Y.; Inagaki, Y.; Yamguchi, K.; Setaka, W. (J. Org. Chem., 2015)

(untitled) - Masuda, T.; Arase, J.; Inagaki, Y.; Kawahata, M.; Yamaguchi, K.; Ohhara, T.; Nakao, A.; Momma, H.; Kwon, E.; Setaka, W. (Cryst. Growth Des., 2016)

(untitled) - Kottas, G. S.; Clarke, L. I.; Horinek, D.; Michl, J. (Chem. Rev., 2005)

(untitled) - Vogelsberg, C. S.; Garcia-Garibay, M. A. (Chem. Soc. Rev., 2012)

(untitled) - Kharel, S.; Joshi, H.; Bierschenk, S.; Stollenz, M.; Taher, D.; Bhuvanesh, N.; Gladysz, J. A. (J. Am. Chem. Soc., 2017)

(untitled) - Alder, R. W.; Butts, C. P.; Orpen, A. G.; Read, D.; Oliva, J. M. (J. Chem. Soc., Perkin Trans. 2, 2001)
and references cited therein.

Diphosphine Dioxide Cages and Hydrogen Peroxide Adducts of Phosphine Oxides: Syntheses and Applications in Surface Science - Hilliard, C. R. (Texas A&M University, 2013)

(untitled) - Kharel, S.; Jia, T.; Bhuvanesh, N.; Reibenspies, J. H.; Blümel, J.; Gladysz, J. A. (Chem. – Asian J., 2018)

(untitled) - Alder, R. W.; East, S. P. (Chem. Rev., 1996)

(untitled) - Park, C. H.; Simmons, H. E. (J. Am. Chem. Soc., 1968)

(untitled) - Stollenz, M.; Barbasiewicz, M.; Nawara-Hultzsch, A. J.; Fiedler, T.; Laddusaw, R. M.; Bhuvanesh, N.; Gladysz, J. A. (Angew. Chem., Int. Ed., 2011)
Angew. Chem. 2011, 123, 6777–6781. doi:10.1002/ange.201100893

(untitled) - Stollenz, M.; Bhuvanesh, N.; Reibenspies, J. H.; Gladysz, J. A. (Organometallics, 2011)

(untitled) - Stollenz, M.; Taher, D.; Bhuvanesh, N.; Reibenspies, J. H.; Baranová, Z.; Gladysz, J. A. (Chem. Commun., 2015)

(untitled) - Nawara-Hultzsch, A. J.; Skopek, K.; Shima, T.; Barbasiewicz, M.; Hess, G. D.; Skaper, D.; Gladysz, J. A. (Z. Naturforsch., B: J. Chem. Sci., 2010)
The yield range given for 1·BH3 reflects the results of repeated preparations since this original report.

(untitled) - Berthod, M.; Favre-Réguillon, A.; Mohamad, J.; Mignani, G.; Docherty, G.; Lemaire, M. (Synlett, 2007)

(untitled) - Shima, T.; Bauer, E. B.; Hampel, F.; Gladysz, J. A. (Dalton Trans., 2004)

(untitled) - Joshi, H.; Kharel, S.; Ehnbom, A.; Skopek, K.; Hess, G. D.; Fiedler, T.; Hampel, F.; Bhuvanesh, N.; Gladysz, J. A. (J. Am. Chem. Soc., 2018)

(untitled) - Grela, K.; Harutyunyan, S.; Michrowska, A. (Angew. Chem., Int. Ed., 2002)
Angew. Chem. 2002, 114, 4210–4212. doi:10.1002/1521-3757(20021104)114:21<4210::AID-ANGE4210>3.0.CO;2-J

(untitled) - Nguyen, T. B.; Castanet, A.-S.; Nguyen, T.-H.; Nguyen, K. P. P.; Bardeau, J.-F.; Gibaud, A.; Mortier, J. (Tetrahedron, 2006)

(untitled) - Woolford, R. G. (Can. J. Chem., 1962)

(untitled) - Taffa, D.; Kathiresan, M.; Walder, L. (Langmuir, 2009)
See Supporting Information.

(untitled) - Matsubara, H.; Tsukida, M.; Ishihara, D.; Kuniyoshi, K.; Ryu, I. (Synlett, 2010)

(untitled) - Soomro, S. A.; Benmouna, R.; Berger, R.; Meier, H. (Eur. J. Org. Chem., 2005)
See for the methodology used to prepare 8.

(untitled) - de Andrade, V. S. C.; de Mattos, M. C. S. (Curr. Org. Synth., 2015)

(untitled) - Stranne, R.; Vasse, J.-L.; Moberg, C. (Org. Lett., 2001)

(untitled) - Staubitz, A.; Robertson, A. P. M.; Sloan, M. E.; Manners, I. (Chem. Rev., 2010)
(see section 4.2.1.1).

(untitled) - Gaumont, A.-C.; Bourumeau, K.; Denis, J.-M.; Guenot, P. (J. Organomet. Chem., 1994)

(untitled) - Pinto, P.; Götz, A. W.; Marconi, G.; Hess, B. A.; Marinetti, A.; Heinemann, F. W.; Zenneck, U. (Organometallics, 2006)

(untitled) - Dahlenburg, L.; Kaunert, A. (Eur. J. Inorg. Chem., 1998)

(untitled) - Däbritz, F.; Theumer, G.; Gruner, M.; Bauer, I. (Tetrahedron, 2009)

(untitled) - Bauer, I.; Habicher, W. D. (Collect. Czech. Chem. Commun., 2004)

(untitled) - Jung, M. E.; Piizzi, G. (Chem. Rev., 2005)

(untitled) - Schuman, M.; Trevitt, M.; Redd, A.; Gouverneur, V. (Angew. Chem., Int. Ed., 2000)
Angew. Chem. 2000, 112, 2604–2607. doi:10.1002/1521-3757(20000717)112:14<2604::AID-ANGE2604>3.0.CO;2-#

(untitled) - Wu, X.; O'Brien, P.; Ellwood, S.; Secci, F.; Kelly, B. (Org. Lett., 2013)